Floating System Tablet Ekstrak Daun Pepaya (Carica papaya L.) Kombinasi Matriks HPMC K4M dan Na CMC - Martinah Martinah; Noval Noval (Jurnal Farmasi & Sains Indonesia, 2022)
Floating system tablets combination of HPMC K4M and Na matrix. CMC and the active substance of papaya leaf extract (Carica papaya L.), by floating in the stomach for a long time and can release the active substance from papaya leaf extract to treat ulcers in the stomach for a certain time to improve its working mechanism. This study used an experimental method with bivariate analysis. Tablet Floating system was made by direct compression method and evaluation includes evaluation of powder, evaluation of physical properties of tablets and evaluation of floating system made in five formulations with different concentrations of HPMC K4M and Na matrix. CMC. The evaluation results of powder, LOD, flow properties, and quiet angle in all formulations met the requirements, while the compressibility test at F4 did not meet the requirements. The resulting tablet has a brown color, is bitter, has a characteristic smell of extract, and is elongated in shape. Tablets in all formulations have uniformity of weight according to the requirements. The results of the hardness test showed that none of the formulations met the requirements, while the friability test of all formulations met the requirements. In the lag time test, all formulations meet the requirements of 1 second, while the floating time results show that all formulations do not meet the requirements. The evaluation results show that the optimal formulation is F5. Combination of HPMC K4M and Na matrix. CMC affects the evaluation of LOD, quiet angle, compressibility, friability, hardness, and floating time. Keywords : Papaya leaf extract (Carica papaya L.), floating system tablets, HPMC K4M and Na.CMC